2017
DOI: 10.1111/joim.12703
|View full text |Cite
|
Sign up to set email alerts
|

Targeted proteomic analysis of habitual coffee consumption

Abstract: The current study supports an inverse association between coffee intake and plasma LEP and CHI3L1 levels. The coffee-CHI3L1 association is novel and warrants further investigation given links between CHI3L1 and health conditions that are also potentially influenced by coffee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
0
5
1
Order By: Relevance
“…A few studies have investigated the relation between coffee consumption and leptin concentrations but reported null (20,67) or inverse associations (64,(68)(69)(70). The current study found that total and caffeinated coffee consumption was associated with lower leptin concentrations.…”
Section: Adipokines and Inflammatory Biomarkerscontrasting
confidence: 38%
“…A few studies have investigated the relation between coffee consumption and leptin concentrations but reported null (20,67) or inverse associations (64,(68)(69)(70). The current study found that total and caffeinated coffee consumption was associated with lower leptin concentrations.…”
Section: Adipokines and Inflammatory Biomarkerscontrasting
confidence: 38%
“…A higher NPX value corresponds to a higher protein level. Samples deviate less than ± 0.3 from the median value for the incubation and detection controls will pass quality control [32]. The mean intra-assay (within-run) and inter-assay (between-run) coefficient of variations were 8% (range 4–13%) and 15% (range 11–39%), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Details on PIVUS and ULSAM blood samples have been described previously. 15, 16 Analyses were performed using the Olink Proseek® Multiplex CVD I 96×96 kit (http://www.olink.com/products/document-download-center/). All samples and runs for PIVUS and ULSAM passed technical quality control.…”
Section: Methodsmentioning
confidence: 99%